Early detection, diagnosis of MIS-C vital - Tan, Ching Siang; Long, Chiau Ming * (New Straits Times Press (M) Bhd., 2022)
In Malaysia, young Covid-19 patients admitted to hospitals have been on the rise: 50,826 children under 12 have tested positive since the middle of last month.